2011
DOI: 10.1007/s10815-011-9684-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Gremlin 1 (GREM1) expression in cumulus cells in young women with diminished ovarian reserve (DOR)

Abstract: Purpose A symbiotic relationship between ovarian granulosa cells (GC) and the developing oocyte is critical. Genetic modulations in GC's can lead to reproductive insufficiency, highlighting the role of GC's in reproductive competence. Utilizing gene expression analyses in cumulus GC's, we attempt to enhance our understanding of mechanisms that may contribute to poor reproductive capacity in young women with diminished ovarian reserve (DOR). MethodsWe measured gremlin 1 (GREM1) gene expression in GC's from infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
15
0
6
Order By: Relevance
“…PCOS compared to non-PCOS (Catteau-Jonard et al 2008, Wei et al 2012, Meng et al 2013, Schmidt et al 2014, Lan et al 2015, endometriosis compared to non-endometriosis , Allegra et al 2014, Barcelos et al 2015 and diminished ovarian reserve compared to normal ovarian reserve (Greenseid et al 2011, Jindal et al 2012, May-Panloup et al 2012) have all been shown to alter gene expression. In fact, PCOS patients with or without insulin resistance were shown to have DRGE compared to non-PCOS normal control patients (Kaur et al 2012).…”
Section: Variables Affecting Granulosa Cell Transcriptomic Profiles Omentioning
confidence: 99%
“…PCOS compared to non-PCOS (Catteau-Jonard et al 2008, Wei et al 2012, Meng et al 2013, Schmidt et al 2014, Lan et al 2015, endometriosis compared to non-endometriosis , Allegra et al 2014, Barcelos et al 2015 and diminished ovarian reserve compared to normal ovarian reserve (Greenseid et al 2011, Jindal et al 2012, May-Panloup et al 2012) have all been shown to alter gene expression. In fact, PCOS patients with or without insulin resistance were shown to have DRGE compared to non-PCOS normal control patients (Kaur et al 2012).…”
Section: Variables Affecting Granulosa Cell Transcriptomic Profiles Omentioning
confidence: 99%
“…Member of family of genes that regulates folliculogenesis, downstream effector of GDF9 Downregulated 4.02-fold in DOR vs control pts [45] differential gene expression between those with DOR and NOR (see Table 2). These genes with differential expression between women with DOR and NOR represent candidates for further research.…”
Section: Differential Gene Expression In Gcsmentioning
confidence: 99%
“…A 15-fold increased expression of the GREM1 gene was seen in cumulus cells stripped from oocytes during IVF with intracytoplasmic sperm injection (ICSI) that resulted in higher quality embryos when compared to lower quality embryos [44]. Jindal et al [45] performed a prospective study examining granulosa cell expression of the GREM1 gene based on these findings using microarray and confirmatory quantitative RT-PCR. They showed a 4.02-fold decreased expression of the GREM1 gene in DOR patients compared to NOR patients.…”
Section: Gremlin 1 (Grem1)mentioning
confidence: 99%
“…Згідно з сучасною концепцією, КК можуть бути надійною моделлю для з'ясування якості ооцита та ефективності протоколу оваріальної гіперстимуляції і опосередковано прогнозувати анеуплоїдію ооцитів, ембріональний розвиток і результат вагітності [2,8,13]. Крім того, аналіз генної експресії в КК може допомогти зрозуміти механізми, які знижують репродуктивну здатність [4,14]. Нині широко використо-вується ПЛР в реальному часі як чутливий і ефективний метод для кількісного визначен-ня окремих транскриптів.…”
Section: оглядиunclassified
“…Ці міжклітинні канали забезпечують трансфер малих моле-кул і сприяють обміну метаболітів глюкози та іонів між ооцитом і КК [1,4]. Генетичні модуляції в КК (як і в гранулярних кліти-нах) можуть призвести до репродуктивної недостатності [14]. Аналіз КК має переваги порівняно з прямою оцінкою ооцита.…”
Section: оглядиunclassified